Osseous Metaplasia in Mucinous Tubular and Spindle Cell Carcinoma of the Kidney: A Case of Massive, Bilateral Tumors - Aeen M. Asghar; Matthew A. Uhlman; Laila Dahmoush; Sundeep Deorah (Case Reports in Urology)
Renal cell carcinoma (RCC) is the most common kidney malignancy, with many histologic subtypes. One of the rare forms of RCC is mucinous tubular and spindle cell carcinoma (MTSCC), which is newly described with limited information on clinical picture and outcome. Heterotopic bone formation (osseous metaplasia) is a rare finding within any renal mass. Here we report a case of a massive, bilateral MTSCC with histologic findings of heterotopic bone formation, which has not been described before.